(untitled) (BIRDEM Medical Journal, 2016)
Melioidosis has recently gained importance as an emerging disease in Bangladesh. It is endemic in South-East Asia and Northern Australia. In Bangladesh few cases have been reported mainly from North-Eastern part of the country (greater Mymensingh area). It can present with varied forms. Here, we are reporting a case of melioidosis, who initially presented with prolonged pyrexia and later hepatic abscess was detected on imaging. Culture of aspirated pus from hepatic lesion revealed growth of Burkholderia pseudomallei. The patient resided in Chittagong hill tracts of Bangladesh. Birdem Med J 2016; 6(1): 43-45